2020
DOI: 10.1161/hypertensionaha.120.15939
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Introduced to Germ-Free Rats Restores Vascular Contractility and Blood Pressure

Abstract: Commensal gut microbiota are strongly correlated with host hemodynamic homeostasis but only broadly associated with cardiovascular health. This includes a general correspondence of quantitative and qualitative shifts in intestinal microbial communities found in hypertensive rat models and human patients. However, the mechanisms by which gut microbes contribute to the function of organs important for blood pressure (BP) control remain unanswered. To examine the direct effects of microbiota on BP, we conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 40 publications
1
37
0
1
Order By: Relevance
“…These data suggest that the vascular system senses the presence (or lack) of microbiota to maintain vascular tone. Overall, these results constitute a fundamental discovery of the essential nature of microbiota in blood pressure regulation (107). Corroborating evidence that microbiota is critical for vascular tone and blood pressure control, male and female GF mice also present a decrease in the contraction of resistance arteries (26).…”
Section: Impact Of the Gut Microbiota On The Cardiovascular Systemmentioning
confidence: 60%
See 1 more Smart Citation
“…These data suggest that the vascular system senses the presence (or lack) of microbiota to maintain vascular tone. Overall, these results constitute a fundamental discovery of the essential nature of microbiota in blood pressure regulation (107). Corroborating evidence that microbiota is critical for vascular tone and blood pressure control, male and female GF mice also present a decrease in the contraction of resistance arteries (26).…”
Section: Impact Of the Gut Microbiota On The Cardiovascular Systemmentioning
confidence: 60%
“…To evaluate the direct effects of microbiota on blood pressure during homeostasis, we conventionalized germ-free (GF) rats with specific pathogen-free rats for ten days (107). The absence of microbiota resulted in relative hypotension in GF rats, compared with their conventionalized counterparts, suggesting an obligatory role of microbiota in blood pressure homeostasis.…”
Section: Impact Of the Gut Microbiota On The Cardiovascular Systemmentioning
confidence: 99%
“…However, this may slightly limit the translatability of these data to future human recipients as some studies have demonstrated variations to GF physiology including alterations in vascular phenotypes and the development of metabolic dysfunction. [40][41][42] Second, our decision to use a single lean and obese donor in each cohort rather than gut microbiota from a mixed group may also reduce the generalizability of the data. Lastly, important questions exist regarding the amount of time that is required for transplantations to elicit physiological changes, as well the duration before those changes begin to wane.…”
Section: Discussionmentioning
confidence: 99%
“… 2 While the primary mode of viral transmission is inhalation of respiratory droplets, the gastrointestinal epithelium is the body site with greatest ACE2 expression. 2 Furthermore, a critical role for gut in COVID-19 pathophysiology is emerging that is potentially relevant for hypertension-COVID-19 comorbidity 2 : (1) ≈30% to 50% COVID-19 of patients manifest gastrointestinal symptoms, often before respiratory symptoms1; (2) infectious severe acute respiratory syndrome coronavirus 2 has been detected in stool, with viral RNA shedding in feces for weeks 3 ; (3) all patients with COVID-19 show altered fecal microbiome and dysbiosis, even those without gastrointestinal symptoms, 4 and some of those bacterial species adversely influence ACE2 4 ; (4) gut mucosa exhibits all components of renin-angiotensin system 2 ; and (5) the intestinal epithelium supports severe acute respiratory syndrome coronavirus 2 replication. 2 These observations led us to hypothesize that increased ACE2 expression in gut epithelium would predispose hypertension patients to COVID-19 infection.…”
Section: Sars-cov-2 Receptor Ace2 (Angiotensin-converting Enzyme 2) Imentioning
confidence: 99%